Pembelajaran Berdiferensiasi dalam Perspektif Konstruktivisme Pada Mata Pelajaran PPKn di SMP Negeri 1 Paguyangan - Baehaqi, M. Lutfi; Andriyani, Desy (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Conventional learning problems that regard teachers as the sole authority of knowledge, sources of knowledge that are textual and rigid, teaching methods that are limited to lectures, lack of effectiveness and role of students, and not channeling students' interests, talents and potential, require different learning strategies. The aim of this research is to describe differentiated learning from a constructivist perspective in Civics subjects at SMP Negeri 1 Paguyangan. The type of research used in this research is descriptive qualitative combined with literature study. The research results show; (1) constructivism is very relevant. (2) things that must be considered in implementing differentiated learning include; availability of supporting learning facilities and infrastructure; availability of tools, media and contextual learning resources; analysis of school and student background; analysis of student needs. (3) the differentiated learning perspective of Civics learning built through constructivism both have very suitable characteristics. (4) differentiated earning from a constructivist perspective has strengths and weaknesses. Keywords: Constructivism, Differentiated Learning, Pancasila and Civic Education